Analysis of H3k27me3 Expression in Malignant Peripheral Nerve Sheath Tumor (MPNST) and Other Spindle Cell Sarcoma Mimicking MPNST - Yordana, William; Evelina, Evelina; Kodariah, Ria (Majalah Patologi Indonesia, 2023)
Malignant Peripheral Nerve Sheath Tumor (MPNST) is a type of spindle cell sarcoma with approximately 5% of all sarcomas. Its diagnosis is challenging due to the absence of specific immunohistochemical markers. Recently, H3K27me3 was discovered as a potential specific immunohistochemical marker to differentiate MPNST from other sarcomas and distinguish between low and high-grade MPNST. Therefore, this research aims to investigate the use of the H3K27me3 as a potential specific marker for Malignant Peripheral Nerve Sheath Tumor (MPNST). A cross-sectional analysis was conducted on 50 cases of sarcomas, including 13 MPNST, 14 synovial sarcomas, 13 dermatofibrosarcoma protuberans (DFSP), and 10 leiomyosarcomas originating from the Department of Anatomical Pathology, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital (FMUI-CMH) from January 2013 to December 2021. H3K27me3 images were obtained and categorized as complete loss when more than 95% of the tumor cells showed loss of nuclear staining. The results found in MPNST showed a loss of H3K27me3 expression, which is statistically significant compared to other sarcomas mimicking MPNST (p=0.021), indicating its potential as a diagnostic marker. There is a difference in the expression of H3K27me3 between the high and low-grade MPNST but it is not statistically significant (p=0.105). This showed that H3K27me3 loss of expression can be used to diagnose MPNST, especially high-grade MPNST, and differentiate it from other sarcomas mimicking MPNST.